Comprendre la dynamique décisionnelle en situation d'interaction évaluative - Sophie Genelot; Jean-François Boyer
The purpose of this research is to analyze the decisional choices made by three first grade teachers during interactive evaluative situations with their students. To do so, we used the teacher interactive thinking model proposed by Wanlin & Crahay (2012) in which the decision is described as a behavioral response to a risk of breaking away from the script planned by the teacher. The identification of the decision-making process is carried out thanks to the identification of gestures (verbal and co-verbal) in the filmed situations. Their analysis allows us to identify a majority of decisions relating to scaffolding, some of which may be the subject of possible dilemmas. In the light of these results we will discuss the qualification of these evaluative situations and propose to rethink the place of the dilemma in the model of the two above-mentioned authors.